The expression and roles of parent-of-origin genes in early embryogenesis of angiosperms - Luo, An; Shi, Ce; Zhang, Liyao; Sun, Meng-Xiang (Frontiers in Plant Science, 2014)
Uniparental transcripts during embryogenesis may arise due to gamete delivery during fertilization or genomic imprinting. Such transcripts have been found in a number of plant species and appear critical for the early development of embryo or endosperm in seeds. Although the regulatory expression mechanism and function of these genes in embryogenesis require further elucidation, recent studies suggest stage-specific and highly dynamic features that might be essential for critical developmental events such as zygotic division and cell fate determination during embryogenesis. Here, we summarize the current work in this field and discuss future research directions.